STRATEGI PEMASARAN AGROINDUSTRI OLAHAN NANAS MADU (Ananas sativus) DI KECAMATAN BELIK KABUPATEN PEMALANG - Dwi Rahmadhanti, Inneke; Retnaningsih, Nugraheni; Arianti, Yoesti Silvana (Universitas Veteran Bangun Nusantara, 2022)
The purpose of this research is to identify and analyze the internal and external environmental factors of MSME honey pineapple processing in Belik District that affect the marketing of pineapple processed products, formulate marketing strategies that can be applied by UMKM honey pineapple processors in marketing their products. The analytical method of this research is descriptive analysis method with data analysis using CPM, SWOT and QSPM matrices. Respondents in this study were owners of UMKM Tiga Sekawan and Madu Jaya as well as consumers of UMKM processed honey pineapple, totaling 4 respondents. The results showed that the CPM score for Tiga Sekawan UMKM was 3.19 and for UMKM Madu Jaya the score was 1.98. SWOT matrix analysis obtained alternative strategies namely SO Strategy: Optimizing production with abundant availability of raw materials, easy-to-obtain production infrastructure, availability of skilled labor, Maintaining cleanliness of production sites, product quality, improving employee performance and creativity, maintaining good relations with resellers and customers WO Strategy: Improve production technology and carry out promotional activities with online media, Form a cooperative and Make capital loans to capital loan service providers to improve the industry. S-T Strategy: Manpower management and cooperation with resellers and retailers by conducting a pre-order system, Expanding the market using online media to expand market reach. W-T Strategy: Increasing packaging innovation and promotion to increase consumer interest and face market competition with other products. Analysis of the strategic priority QSPM matrix in strategy II, increasing packaging innovation and also promotions to increase consumer interest.